2016
DOI: 10.1016/j.neurobiolaging.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Obesity associated with increased brain age from midlife

Abstract: Common mechanisms in aging and obesity are hypothesized to increase susceptibility to neurodegeneration, however, direct evidence in support of this hypothesis is lacking. We therefore performed a cross-sectional analysis of magnetic resonance image-based brain structure on a population-based cohort of healthy adults. Study participants were originally part of the Cambridge Centre for Ageing and Neuroscience (Cam-CAN) and included 527 individuals aged 20–87 years. Cortical reconstruction techniques were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
133
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(155 citation statements)
references
References 71 publications
13
133
4
Order By: Relevance
“…Obesity is associated with age‐related functional declines in the brain, which are characterized by decreased executive functions, loss of memory, and impaired processing speed . At the anatomical level, results from the cortical reconstruction of 527 individuals have revealed that excess adiposity is associated with cerebral white‐matter atrophy corresponding to a 10‐year older brain in people with obesity . Obesity may accelerate the onset of neurodegenerative phenotypes through the aggregation of α‐synuclein, pathological protein modifications, and neuroinflammation in mice .…”
Section: Obesity Drives Ageing At Multiple Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity is associated with age‐related functional declines in the brain, which are characterized by decreased executive functions, loss of memory, and impaired processing speed . At the anatomical level, results from the cortical reconstruction of 527 individuals have revealed that excess adiposity is associated with cerebral white‐matter atrophy corresponding to a 10‐year older brain in people with obesity . Obesity may accelerate the onset of neurodegenerative phenotypes through the aggregation of α‐synuclein, pathological protein modifications, and neuroinflammation in mice .…”
Section: Obesity Drives Ageing At Multiple Levelsmentioning
confidence: 99%
“…Human-brain 96 Cerebral white-matter volume Individuals with obesity were associated with brain atrophy and this effect was found to be strongest at the age of 40, corresponding to an increase in white matter-based brain age of 10 years.…”
Section: Ageing Of Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Work is beginning to appear on factors such as exercise, obesity (Baxendale et al, 2015; Hamed, 2015), vascular risk (Hamed, 2015) and metabolic abnormalities in epilepsy—some related to cognitive status (Baxendale et al, 2015). These are important developments as recent population based investigation has shown atrophy of cerebral white- matter volume to be associated with overweight and obese individuals with maximal effects in middle- age corresponding to an estimated increase of brain age of 10 years (Ronan et al, 2016). Relatedly, population based investigations have shown elevated vascular risk factors that could assist in explaining the high risk of cerebral and cardiac vascular disease in epilepsy patients (e.g., hyperlipidemia) (Harnod, Chen, Li, Sung, & Kao, 2014), which may be due in part to untoward antiepileptic medications (Brodie et al, 2013).…”
Section: Where Is the Neuropsychology Of Epilepsy Headed During The Nmentioning
confidence: 99%
“…Further, obesity is associated with increased brain age. 7 In addition, Type 2 Diabetes per se accelerates…”
Section: Introductionmentioning
confidence: 99%